Which Market Entry and Product Line Strategies Ought Organisations to Adopt for Emerging Economies? - Cherian, Joseph; Crooker, Karen J.; Knight, Peter; McPhaul, James B.; Manion, Michael T. (Organizations and Markets in Emerging Economies, 2010)
Emerging economies offer tremendous potential for organisations seeking to expand globally and to attain the associated rewards. However, organisations differ in their entrepreneurial tendencies to enter new markets and to introduce new products in emerging economies. Organisations also differ in their abilities to manage their development programs, that is, their execution of different types of projects that lead to success in emerging markets. Finally, organisations differ in which overall measures of program performance are consistent with their strategic objectives. This study provides a literature foundation and conceptual framework designed to understand which market entry and product line strategies and performance measures are appropriate for organisations pursuing strategic success in emerging markets. This study sets forward grounded propositions that different strategic types will vary in their market entry and product line strategies, in the project composition of their development programs, and in the orientations of performance measures used to evaluate their development programs. Prospectors, according to type, will enter emerging economies by introducing new product lines to new customer types, and by emphasizing new-to-the-world products. They will evaluate their development programs with Growth-oriented performance measures. Defenders will more typically occupy secure niches within emerging economies by emphasizing product improvement and cost reduction projects for current types of customers. They will evaluate their development programs with Efficiency-oriented performance measures. Analyzers will either target new customer types with proven products, or serve an existing market niche with new product lines. They will evaluate their development program performance with Strategy-oriented measures.